Fortification of salted chicken eggs with iodine - Arguez, Lugin Paul S.
The study was conducted using a fixed-effects single-factor completely randomized design to determine the effects of iodone fortification on the physico-chemical properties, microbial load, and consumer acceptability of salted chicken eggs.